The Contributions of Shellfish Aquaculture to Global Food Security: Assessing Its Characteristics From a Future Food Perspective - Azra, Mohamad Nor; Okomoda, Victor Tosin; Tabatabaei, Meisam; Hassan, Marina; Ikhwanuddin, Mhd (Frontiers in Marine Science, 2021)
The United Nation's 2030 development agenda adopted in 2015 outlines 17 Sustainable Development Goals (SDGs), and the organization has continued to put food security in the center of its vocalization. Aquaculture is currently the fastest-growing food production sector globally and a sustainable option for attaining food security. Food as a basic necessity for man's survival is always a timely issue. Hence, owing to aquaculture's unique role, it is expected that the demand for aquatic products (especially seafood) will continue to increase due to geometric population growth. Many seafood products are among the critical protein sources in the world. This is partly because they have micronutrients and essential fatty acids that are not present in land-based protein sources. According to the Food and Agriculture Organization, shellfish is one of the main cultured aquaculture groups in the world. Hence, the development of shellfish aquaculture has an important role in sustainable food supply and food security. In this article, an overview of the current and projected contributions of shellfish aquaculture to global food security is presented. Apparently, shellfish aquaculture in the next few decades will have to be intensified to bridge the gap between demand and supply in a cost-effective manner. Also, food waste would have to be reduced and natural resources should be used more efficiently to minimise the negative impacts on aquaculture on the environment.